A study on free-standing 3C-SiC bipolar power diodes - Mike Jennings (Applied Physics Letters, 2021)
A low p–n built-in potential (1.75 V) makes 3C-SiC an attractive choice for medium voltage bipolar or charge balanced devices. Until recently, most 3C-SiC had been grown on Si, and power device fabrication had, therefore, been hindered by issues, such as high defect density and limited processing temperature, while devices were necessarily limited to lateral structures. In this work, we present the fabrication and characterization of a vertical PiN diode using bulk 3C-SiC material. A p-type ohmic contact was obtained on Al implanted regions with a specific contact resistance ∼10−3 Ω cm2. The fabricated PiN diode has a low forward voltage drop of 2.7 V at 1000 A/cm2, and the on–off ratio at ±3 V is as high as 109. An ideality factor of 1.83–1.99 was achieved, and a blocking voltage of ∼110 V was observed using a single-zone junction termination design.